Embolization of Meningiomas: Comparison of Safety between Calibrated Microspheres and Polyvinyl-Alcohol Particles as Embolic Agents - Sluzewski, M. (AJNR Am J Neuroradiol, 2013)
BACKGROUND AND PURPOSE: During embolization of meningiomas, intratumoral hemorrhagic complications may occur, especially with the use of small particle sizes. We compared the rate of hemorrhagic complications in 55 patients embolized with 400-μm calibrated microspheres (Embozene) with a historical cohort of 198 patients embolized with smaller PVA particles. MATERIALS AND METHODS: Between September 2009 and February 2012, fifty-five patients with 55 meningiomas were embolized with 400-μm calibrated microspheres. Indications for embolization were preoperative in 47 and before radiosurgery in 2 patients; and in 6 patients, embolization was offered as sole therapy. There were 35 women and 20 men with a mean age of 60.3 years. Mean meningioma diameter was 53 mm (range, 23–97 mm). Hemorrhagic complications were recorded. RESULTS: There were no hemorrhagic complications in the 55 embolized patients (0%; 95% CI, 0.0%–7.8%). The difference in complication rates between 400-μm calibrated microspheres in this study (0 of 55, 0%) and small PVA particles (45–150 μm) in the historical cohort (9 of 108, 8.3%) was just short of significance (P = .066). The difference in complication rates between 400-μm calibrated microspheres (0 of 55, 0%) and larger PVA particles (150–250 μm) in the historical cohort (1 of 93, 1.1%) was not significant (P = .8). CONCLUSIONS: In this series, embolization of meningiomas by using large (400-μm) calibrated microspheres did not result in any hemorrhagic complications.